Hubungan Aktivitas Fisik dan Tingkat Stres terhadap Kualitas Tidur pada Pasien Post Operasi - Maya Ardilla Siregar; Mhd Adi Setiawan Aritonang; Yaumil Hafsani Siregar (Universitas Muhamadiyah Manado, 2024)
Sleep quality is very important for health, good quality sleep is needed by patients in healing and physical recovery. Sleep quality can occur through the pain felt and physical activity as well as stress levels. The aim of this study was to determine the relationship between physical activity and stress levels on the sleep quality of post-operative patients at Mitra Medika Tanjung Mulia RSU. The research design used in this study used an analytical survey with a cross sectional approach using the chi-square test. The population in this study were post-operative patients at RSU Mitra Medika Medan, with a population of 400 people, while the sample used was random sampling, totaling 80 respondents. The results of the study show that physical activity affects sleep quality (p value = 0.046), and stress levels affect sleep quality (p value = 0.029). Conclusion: There is a relationship between physical activity and stress levels on sleep quality in post-operative patients.